Testosterone suppresses ventricular remodeling and improves left ventricular function in rats following myocardial infarction - WANG, XIAO-FEI (Exp Ther Med, 2015)
Men with congestive heart failure (CHF) have relatively low testosterone levels. Several studies demonstrated that testosterone treatment increases cardiac output and reduces peripheral vascular resistance. However, the effects of testosterone on heart function, cardiomyocyte apoptosis and ventricular remodeling have not been fully elucidated. This study was conducted to investigate the effects of testosterone on heart function, cardiomyocyte apoptosis and ventricular remodeling in male rats post-myocardial infarction. A total of 86 male rats were randomly assigned to undergo ligation of the coronary artery (n=70) or pseudosurgery (n=16). After 6 weeks, a left ventricular ejection fraction (LVEF) of ≤45% was defined as a successful model of CHF. The model rats were randomly assigned to 3 groups, namely low-dose testosterone (TU), high-dose TU and placebo (PL) groups. After treatment for 12 weeks, the expression of several mRNA transcripts in myocardial tissue was measured by quantitative polymerase chain reaction. Immunofluorescence was used to measure myocardial caspase-3 expression. Compared to the PL group, LVEF was significantly improved in the TU treatment groups. Moreover, the mRNA expression of atrial natriuretic peptide, brain natriuretic peptide, matrix metalloproteinase-2 and sarcoendoplasmic reticulum Ca(2+)-ATPase 2a was significantly reduced, while the mRNA expression of glycogen synthase kinase 3β and tissue inhibitor of metalloproteinase-2 was markedly increased in the TU groups. TU treatment also significantly reduced caspase-3 expression. Therefore, different doses of TU suppressed ventricular remodeling and improved left ventricular function, reduced apoptosis and prevented mortality in a CHF rat model.